SLOPE STABILITY ANALYSIS IN ANDESITE STONE MINING ROLAS NUSANTARA TAMBANG Ltd. IN PASURUAN REGENCY - Yudho Dwi Galih Cahyono; Ratih Hardini Kusuma Putri; Aprilia Dwi Astuti (Institut Teknologi Adhi Tama Surabaya, 2022)
In mining activities Rolas Nusantara Tambang Ltd. needs to do a slope stability analysis because at that location there has never been a study on the condition of the slopes. In addition, there are several problems that can cause unstable slopes such as slope geometry that is too upright, the presence of discontinuity fields and mining locations that are close to several active volcanoes in East Java, namely Mount Semeru and Mount Bromo so that the potential for earthquakes and vibrations is high and can be affect the stability of the slopes at that location. This study aims to analyze slope stability using the Janbu method in calculating the factor of safety and the Monte Carlo method for the probability of landslides. From the results of the study, the actual slope safety factor (FK) was 1.703 and the probability of landslide (PK) was 0.000% with a slope height of 12 meters and a slope of 850. Then recommendations were given for the overall slope with an overall height of 36 meters and an overall slope of 570, the factor value was obtained. safety (FK) of 2.170 and probability of landslide (PK) of 0.000%. From these results it can be concluded that the slope conditions are in the safe category.